2020
DOI: 10.1101/2020.03.16.994400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a new class of liver receptor homolog-1 (LRH-1) agonists by photoredox conjugate addition

Abstract: Article history:Received Revised Accepted Available online LRH-1 is a nuclear receptor that regulates lipid metabolism and homeostasis, making it an attractive target for the treatment of diabetes and non-alcoholic fatty liver disease. Building on recent structural information about ligand binding from our labs, we have designed a series of new LRH-1 agonists that further engage LRH-1 through added polar interactions. While the current synthetic approach to this scaffold has, in large part, allowed for decorat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…We have shown that polar groups at R1 in 6HP ligands act as anchors to lock this class of compound in very similar binding poses. (22,(24)(25)(26)(27). Therefore, ligands without experimentally determined structures were docked into the binding pocket such that the 6HP cores were aligned (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that polar groups at R1 in 6HP ligands act as anchors to lock this class of compound in very similar binding poses. (22,(24)(25)(26)(27). Therefore, ligands without experimentally determined structures were docked into the binding pocket such that the 6HP cores were aligned (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, NRs interact with many coregulators, which likely utilize different allosteric mechanisms. Tif2 has been crystallized with many LRH-1-ligand complexes, and it interacts with LRH-1 in the presence of both strong and weak agonists and when the receptor is unliganded (20, 21,[24][25][26]29,36,37). This makes Tif2 well-suited for studying allosteric signaling by ligands with a wide range of activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to demarking differences between active and inactive compounds, the coregulator recruitment pattern of 9CA and 10CA also differs from that of 6N and 6Na, LRH-1 agonists that share the 6HP scaffold but are modified elsewhere on the molecule (Figure S1) (Cornelison et al, 2020;Mays et al, 2019). Unsupervised hierarchical clustering of the data shows a striking separation by ligand class: the most structurally similar ligands cluster together (Figure 3D).…”
Section: Modifications Improve Binding Affinity and Activitymentioning
confidence: 99%
“…In contrast, the synthetic LRH-1 agonist RJW100 binds deep in the pocket (Figure 1A). We previously focused on strengthening deep pocket interactions made by RJW100, resulting in the discovery of the agonists 6N and 6Na (Figure S1) (Cornelison et al, 2020;Mays et al, 2019). For the PL mimics, we used an alternative approach, seeking to promote interactions near the mouth of the pocket.…”
Section: Structure-guided Design Of Pl Mimicsmentioning
confidence: 99%
“…Accordingly, administration of dilauroyl phosphatidylcholine (DLPC, the natural ligand of LRH-1/NR5A2) was shown to decrease hepatic steatosis and improve glucose homeostasis in two mouse models of insulin resistance and T2DM 10 . These results prompted the development of hybrid phospholipid mimics as well as small non-polar bicyclic compounds that act as potent LRH-1/NR5A2 ligands 11,12,13 . Based on one of these published structures able to bind to the ligand binding pocket of NR5A2/LRH1, we synthesized a small chemical agonist of LRH-1/NR5A2, denoted as BL001, and assessed its anti-diabetic therapeutic value for T1DM.…”
Section: Introductionmentioning
confidence: 99%